Time and cost burden associated with docetaxel in patients with metastatic castration-sensitive prostate cancer initiating an androgen receptor pathway inhibitor-based regimen - Sentana-Lledo, Daniel; Gupta, Arjun; Rossi, Carmine; Burbage, Sabree; Korsiak, Jill; Diaz, Lilian; Wong, Gordon; Pilon, Dominic; Khilfeh, Ibrahim; Morgans, Alicia K. (Frontiers in Oncology, 2025)
BackgroundThe triplet combination of chemotherapy (docetaxel), androgen receptor pathway inhibitors (ARPI), and androgen deprivation therapy has recently become a recommended approach to treat metastatic castration-sensitive prostate cancer (mCSPC). This study aimed to compare the incremental time and cost burden of adding docetaxel to ARPI-based treatment among patients with mCSPC receiving chemotherapy-containing regimens (CCR) and non–chemotherapy-containing regimens (NCR) in the United States.MethodsClinical data from community urology practices linked with claims data (1/1/2016–12/31/2023) were used to select patients initiating a CCR or NCR. Outcomes, including time spent managing mCSPC (days with prostate cancer-related resource utilization or management care) and healthcare costs, were compared between balanced cohorts using weighted multivariable Poisson and linear regressions.Results126 CCR and 837 NCR patients (mean age 64.7 years, 52.6% White, 14.4% Black) were followed for a mean of 6.3 (CCR) and 6.8 (NCR) months. The CCR cohort spent on average 4.1 days per-patient-per-month (PPPM) managing mCSPC vs 3.3 days PPPM in the NCR cohort (rate ratio: 1.18; 95% confidence interval [CI]; 1.03, 1.34). Mean all-cause total healthcare costs were $17,833 PPPM in the CCR cohort and $11,527 PPPM in the NCR cohort (weighted adjusted cost difference: $6,184; 95% CI: 3,515, 8,517).ConclusionsPatients initiating a CCR experienced greater time burden managing mCSPC and higher healthcare costs than those initiating an NCR. These findings support counseling expressing these differences in burden in mCSPC treatment decision-making conversations.